2011
DOI: 10.1177/0883073810397631
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric Status Migrainosus

Abstract: The impact of treatment given upon discharge on the "bounce back" rate was ascertained in children presenting at the emergency department for treatment of status migrainosus. All children ages 8 to 17 years old presenting to an emergency department in 2008 who were treated for status migrainosus and discharged home were included. Of the total of 187 patients, 21 patients (11.2%) bounced back. Treatment given was not associated with the bounce back rate. The only factors reaching significance were the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…The most common agents are prochlorperazine, chlorpromazine, promethazine, and metoclopramide. Although metoclopramide was the most common agent in previous reports of pediatric 5,8 and adult 19 migraine treatment in the ED setting, we observed that prochlorperazine and metoclopramide are used with equal frequency. Previous reports from adults have suggested that prochlorperazine might be more efficacious than metoclopramide, 20 and prochlorperazine's safety and effectiveness has been previously reported.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The most common agents are prochlorperazine, chlorpromazine, promethazine, and metoclopramide. Although metoclopramide was the most common agent in previous reports of pediatric 5,8 and adult 19 migraine treatment in the ED setting, we observed that prochlorperazine and metoclopramide are used with equal frequency. Previous reports from adults have suggested that prochlorperazine might be more efficacious than metoclopramide, 20 and prochlorperazine's safety and effectiveness has been previously reported.…”
Section: Discussionmentioning
confidence: 56%
“…5,8 Triptans, a serotonin receptor agonist, have been increasingly used for treatment of acute migraine. Although they have the greatest value early in the course of illness, 24 most children with migraine present to the ED after experiencing prolonged symptoms at home.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations